The effect of environmental stressors on growth in fish and its endocrine control - Canosa, Luis Fabián; Bertucci, Juan Ignacio (Frontiers in Endocrinology, 2023)
Fish body growth is a trait of a mayor importance for individual survival and reproduction. It has implication in population, ecology, and evolution. Somatic growth is controlled by GH/IGFs endocrine axis and is influenced by nutrition, feeding and reproductive regulating hormones as well as abiotic factors such as temperature, oxygen levels and salinity. Global climate change and anthropogenic pollutants will modify environmental condition affecting directly or indirectly fish growth performance. In the present review we offer an overview of the somatic growth, its interplay with feeding regulatory axis and summarize the effects of global warming and main anthropogenic pollutants on these endocrine axes.